2023
DOI: 10.1101/2023.12.20.572656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling cellular heterogeneity and fructose transporter expression in the rat nephron by integrating single-cell and microdissected tubule segment transcriptomes

Ronghao Zhang,
Darshan Aatmaram Jadhav,
Benjamin Kramer
et al.

Abstract: Single-cell RNA sequencing (scRNAseq) is a crucial tool in kidney research. These technologies cluster cells according to transcriptome similarity, irrespective of the anatomical location and ordering within the nephron. Thus, a cluster transcriptome may obscure heterogeneity of the cell population within a nephron segment. Elevated dietary fructose leads to salt-sensitive hypertension, in part by fructose reabsorption in the proximal tubule (PT). However, organization of the four known fructose transporters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(77 reference statements)
0
1
0
Order By: Relevance
“…A preprint publication recently demonstrated that SGLT4 expression in rat proximal tubules is similar to that of human orthologues. 45 Single-cell RNA-sequencing data show that the expression patterns of SGLT5 and SGLT4 in rats are highly correlated to those of humans. In both species, the expression of SGLT5 is larger in the S2 and S3 cell clusters as compared with S1.…”
Section: Discussionmentioning
confidence: 99%
“…A preprint publication recently demonstrated that SGLT4 expression in rat proximal tubules is similar to that of human orthologues. 45 Single-cell RNA-sequencing data show that the expression patterns of SGLT5 and SGLT4 in rats are highly correlated to those of humans. In both species, the expression of SGLT5 is larger in the S2 and S3 cell clusters as compared with S1.…”
Section: Discussionmentioning
confidence: 99%